El procedimiento directo en el Código Orgánico Integral Penal y la vulneración del derecho a la defensa. - Días Ledesma, Daniel Fernando (2022)
The direct procedure, based on the principles of speed and procedural economy, sought to expedite criminal proceedings, however, at the time of its applicability, it violates a basic guarantee of due and fair process, the right to defense. Therefore, a description of the legal and doctrinal elements of the direct procedure was made in order to understand its applicability. Likewise, the right to defense was analyzed, in the basic guarantees of having sufficient time to prepare the defense and to have an impartial judge, from a constitutional and conventional vision to understand how to make its protection effective. The type of research is applied, the method had a qualitative approach with inductive logic and correlational scope, using documentary analysis and interview as data collection techniques. After that, it was established that at the moment of the application of the direct procedure the right to defense is violated. Therefore, per se to a legal reform, it was determined that judges have the obligation to respect the principle of constitutional supremacy and apply the Constitution directly, without being able to allege lack of norm. Even, if they consider it necessary, they could inapply a norm without expelling it from the legal system